Reactions of Stabilized Aliphatic Carbanions with Esters of Formic Acid in the Gas Phase. Issue 3 (June 2015) - Wileńska, Beata; Świder, Paweł; Danikiewicz, Witold
The reactions of nitromethane, acetonitrile, and ethyl acetate carbanions with formic acid esters were investigated in the gas phase by mass spectrometry and quantum chemical calculations. It was found that the carbanion of nitromethane practically does not react with formic acid esters and only traces of the Claisen-type addition–elimination reaction product were observed. In the case of the deprotonated acetonitrile, the Claisen-type condensation that yielded the carbanion of cyanoacetaldehyde proceeded almost quantitatively for all the studied formates. Other products, like the Riveros reaction product, were observed in minor amounts. The ethyl acetate carbanion reacts with formates in a much more complex way because it decomposes in a collision cell, yielding the deprotonated ketene anion, which also can react with formic acid esters. Consequently, the Claisen condensation reaction products of both anions were observed as well as the products of other reactions. All the proposed reaction pathways were confirmed by quantum chemical calculations, including the transition-state energies.